2021
DOI: 10.1097/wno.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Double Vision and Gait Ataxia in an Immunocompetent 9-Year-Old Girl With Intracranial Phaeohyphomycosis

Abstract: A 9-year-old girl presented with morning headaches associated with vomiting, gait ataxia, and facial and ocular motor nerve palsies. Her initial imaging was concerning for demyelinating disease. After extensive infectious and rheumatologic workup returned negative, she was treated twice with intravenous immunoglobulin and intravenous steroids with near-complete resolution each time. She returned, however, with worsening neurologic deficits and imaging revealing focal ischemic infarction in the brainstem as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Plasma mcf-DNA sequencing revealed colonization with Cladophialophora bantiana . The patient was managed with voriconazole, flucytosine, and intraventricular amphotericin B [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma mcf-DNA sequencing revealed colonization with Cladophialophora bantiana . The patient was managed with voriconazole, flucytosine, and intraventricular amphotericin B [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pareek et al (2021) reported a case of a nine-year-old female presenting with occipital headache, gait ataxia, and visual disturbance. The patient had 20/40 visual acuity in the left eye, right-sided dysmetria, and multiple cranial nerve deficits.…”
mentioning
confidence: 99%